Literary Translations from Latvian and Lithuanian into Italian in 2019–2023 - Cerri, Adriano (Vertimo studijos, 2024)
The article presents an overview of translations from Lithuanian and Latvian into Italian during the last five years (2019–2023). It aims to update previous data on Baltic literatures in Italy and to examine their current status. Additionally, it seeks to identify the main differences between the reception of Lithuanian and Latvian literature in Italy and to assess recent developments and emerging trends in this field. Translations of Lithuanian and Latvian works into Italian published during the analysed period are first reviewed by genre: prose, children’s literature, poetry, essays, and scientific literature. Information about upcoming translations known to the author is also provided. Statistical data are presented and compared with data from earlier periods. The analysis reveals a significant recent increase in translations of children’s and young people’s literature. However, the period 2019–2023 has also seen the publication of notable novels and short story collections from both languages, as well as poetry anthologies and important scholarly works originally written in Lithuanian. The statistics indicate that the past five years have been as productive as the preceding five-year period. Given the very small number of translators working with these languages, this is a positive achievement. Another encouraging trend is that Baltic literatures are beginning to attract the attention of larger publishing houses, which can provide better visibility for these works.